The province of Espirito Santo versus “reigning epidemics”: state actions and popular mobilization in the passage of yellow fever and cholera (1850-1856) - Franco, Sebastião Pimentel; Nogueira, André (História: Questões e Debates, 2017)
The present article aims to discuss the control and assistance practices of the Province of Espírito Santo in the context of the epidemic surges of yellow fever and cholera. In line with the argumentation of Rosemberg (1992), facing an epidemics is an extreme and disconcerting experience, which forces a change in social habits and in the most elementary forms of arrangement of a certain collectivity, and which obviously causes pain and death as well. In the same manner, an epidemics also occasions multifaceted actions and reflections – “lessons”, to use the author’s term, that aim to respond and to “get rid” of it. Thus, we are interested in analyzing the actions of the provincial government so as to tackle the inconvenient visitations of the epidemics of yellow fever and cholera as well as the equally varied and resistant forms through which the population of the province protested in the face of such illnesses. Our interpretation is based in the analysis of administrative documents (mail, reports, etc.) as well as in the news broadcasted by the Correio da Victória, the only newspaper that circulated in the Province during the period in question.